2003
DOI: 10.1103/physrevb.68.014418
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid domain walls and antiferromagnetic domains in exchange-coupled ferromagnet/antiferromagnet bilayers

Abstract: Magneto-optical imaging has revealed new features crucial for the understanding of the exchange bias phenomenon. We have observed hybrid domain walls consisting of ferromagnetic ͑FM͒ and antiferromagnetic sections and their evolution. The external magnetic field moves only the ferromagnetic section of the hybrid domain walls, leading to the formation of an exchange spring parallel to the interface. The nucleation and unwinding of the exchange spring occur at different locations and its propagation depends on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
1
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 17 publications
1
36
1
4
Order By: Relevance
“…Such an uncompensated AF spin has both parallel and antiparallel AF neighbors, and, therefore, is in a frustrated state. Similar configurations may exist if other mechanisms are involved in the exchange anisotropy, such as spin-flop coupling [18,19], hybrid F-AF domain walls [20] or partial AF domains [21]. The frustrated state of the interfacial AF spins in combination with the reduced AF coordination number at the interface leads to the situation, when T N int is less than T N , and the interfacial AF spins can be reoriented by an external field above this temperature, and below T N [22].…”
Section: Figmentioning
confidence: 99%
“…Such an uncompensated AF spin has both parallel and antiparallel AF neighbors, and, therefore, is in a frustrated state. Similar configurations may exist if other mechanisms are involved in the exchange anisotropy, such as spin-flop coupling [18,19], hybrid F-AF domain walls [20] or partial AF domains [21]. The frustrated state of the interfacial AF spins in combination with the reduced AF coordination number at the interface leads to the situation, when T N int is less than T N , and the interfacial AF spins can be reoriented by an external field above this temperature, and below T N [22].…”
Section: Figmentioning
confidence: 99%
“…[16] Experimentally, it is not apparent to detect the influence of AFM spin orientation on training effect. For Co/CoO system, several techniques have been applied to study AFM domains [17], and applied in-plane magnetic field perpendicular to the cooling field largely restores the untrained state [3]. So, the reappearance of untrained state will promote us obtain the training effect mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…11 In practice, the situation may be more complex due to the presence of uncompensated spins at the AFM surface as manifested in the strong exchange coupling between AFM and FM, 2 and formation of domain walls in the AFM layer interacting with a FM. [22][23][24] Although it is not straightforward to probe its existence, domain walls may also form in the AFM layer of AFM/S bilayers due to magnetostatic interactions. In a recent work, we have found that magnetostatic interactions between Nb and IrMn/NiFe in a Nb/IrMn/NiFe trilayer induces instability in the exchange bias field at the IrMn/NiFe interfaces.…”
mentioning
confidence: 99%
“…24,27 The latter could be developed in the thin IrMn layer through interaction with Nb below T c . The random distribution of these net surface or volumetric spins 22,23 naturally leads to a non-uniform stray field across the sample plane. The proximity effect is less sensitive to the random distribution of magnetic domains as it is dominantly a surface effect.…”
mentioning
confidence: 99%